Small Angle Scattering and Diffraction - Franco, Margareth K. K. D.; Yokaichiya, Fabiano (IntechOpen, 2018)
Reasoned and based on the difference between discovery and invention, according to the traditional conception, science can be distinguished between basic science and applied science. Nevertheless, we know that the sciences are inseparable. A century or more ago, Louis Pasteur said "there is no applied science, there are applications of science." With this assertion, he establishes the logic of complementarity between them. Science certainly goes beyond its own material application and brings us to issues that have intrigued humanity for a long time. During the many years that we have been working with techniques of material characterization, we observed that this complementarity was not always understood by the researchers. In line with the reasoning that the technique joined with science generates technology, the application of techniques that use x-ray and neutron sources seems to us of fundamental importance for the development of technology. In this way, we present in this book how the existing technology of material characterization can contribute to science and applied technology. The authors who contributed with this book sought to show the importance of applying the existing techniques in the development of their works.